Effect of Pre-harvest Application of Calcium Chloride and Gibberellic Acid on Shelf-Life and Post-Harvest Quality of Apricot (Prunus armeniaca L.) Cv. Harcot - S Lal (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2011)
Pre-harvest application of calcium chloride (0.5, 1.0, and 1.5 %) and gibberellic acid(10, 20 and 30 ppm) at 80% blooming, fruit-set and at 15 days before harvest were carried out on 5-year old trees of apricot cv. Harcot. All the treatments significantly reduced physiological loss in fruit weight, fruit diameter and spoilage percentage during storage. However, CaCl2 @ 1.5% was found to be most effective in minimizing weight loss in fruits during storage compared to Control. Fruits quality (TSS, titrable acidity, TSS/TA, ascorbic acid, total sugar, etc.) was also found to be better (even at 8 days of storage at ambient condition with this treatment) compared to Control. Hence, it can be concluded that pre-harvest foliar application in apricot cv. Harcot with CaCl2 @ 1.5% at three stages, i.e., 80% blooming, at fruit-set and 15 days before harvest, enhances shelf-life of the fruit from 3-5 days storage to 8 days storage, and can maintain good fruit quality under ambient storage-condition for up to 8 days.